2022
DOI: 10.1111/joor.13381
|View full text |Cite
|
Sign up to set email alerts
|

Do cone‐beam computed tomography low‐dose protocols affect the evaluation of the temporomandibular joint?

Abstract: Background: There is no established acquisition protocol based on scientific evidence for the acquisition of cone-beam computed tomography (CBCT) exams to evaluate the temporomandibular joint (TMJ). Objectives:To evaluate the influence of acquisition protocols and jaw positioning on the diagnostic accuracy of TMJ condylar morphological alterations (CMA), dimension, position and excursion.Methods: Thirty-six TMJs on 18 dry skulls were imaged using a CBCT unit (OP300 Maxio, Instrumentarium, Tuusula, Finland) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…The later might be related to the high complexity and difficulty in detecting small and discrete alterations of the condyle and also classifying among different types. Also, previous studies have shown low intra and inter‐evaluators agreement when assessing condylar morphological alterations 29,30 . Furthermore, when looking to our outcomes, it is possible to observe that lower severity alterations prevailed above higher severity alterations, which implies in a more difficult diagnosis.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The later might be related to the high complexity and difficulty in detecting small and discrete alterations of the condyle and also classifying among different types. Also, previous studies have shown low intra and inter‐evaluators agreement when assessing condylar morphological alterations 29,30 . Furthermore, when looking to our outcomes, it is possible to observe that lower severity alterations prevailed above higher severity alterations, which implies in a more difficult diagnosis.…”
Section: Discussionmentioning
confidence: 69%
“…Also, previous studies have shown low intra and inter-evaluators agreement when assessing condylar morphological alterations. 29,30 Furthermore, when looking to our outcomes, it is possible to observe that lower severity alterations prevailed above higher severity alterations, which implies in a more difficult diagnosis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, Reis et al (2022) stated that acquisition protocols (voxel size and mA) and jaw position (closed and open) did not influence the detection of TMJ degenerative joint disease changes alterations (de Oliveira Reis et al, 2022). …”
mentioning
confidence: 99%